American Medical Society for Sports Medicine Sports Ultrasound Curriculum for Sports Medicine Fellowships. Issue 4 (July 2021) - Hall, Mederic M.; Bernhardt, David T.; Finnoff, Jonathan T.; Hoffman, Douglas F.; Hrubes, Melody R.; Mautner, Kenneth R.; Rao, Ashwin L.; Ray, Jeremiah W.; Smith, Jay; Waterbrook, Anna L.
Abstract : Abstract: Sports ultrasound is commonly used by sports medicine physicians to enhance diagnostic and procedural accuracy. This expert consensus statement serves as an update to the 2015 American Medical Society for Sports Medicine recommended sports ultrasound curriculum for sports medicine fellowships. Although written in the context of the American sports medicine fellowship training model, we present a stepwise progression in both diagnostic and interventional sports ultrasound that may be applicable to the broader sports medicine community. The curriculum is divided into 12 units with each unit including didactic instructional sessions, practical hands-on instruction, independent scanning practice sessions, and mentored clinical experience. To assist with prioritization of learning, we have organized relevant pathology and procedures as essential, desirable, and optional. The expanded content can serve as an outline for continuing education postfellowship or for any physician to further advance their sports ultrasound knowledge and skill. We also provide updated scanning protocols, sample milestones, and a sample objective structured clinical examination (OSCE) to aid fellowships with implementation of the curriculum and ongoing assessment of fellow progress. Abstract : Supplemental Digital Content is Available in the Text.